Perioperative blood glucose in a paediatric daycase facility: Effects of fasting and maintenance fluid - Anthony Taiwo Adenekan (Wolters Kluwer Medknow Publications, 2014)
Background: Many Children are daily exposed to prolonged preoperative fasting time. The choice of intraoperative maintenance fluid continues to be an issue of controversy. This study assesses the duration of preoperative fast among children undergoing ambulatory surgery and the appropriateness of the maintenance solutions used. Patients and Methods: Seventy-eight children undergoing ambulatory surgery were prospectively randomised to receive lactated Ringer's (LR) solution or 4.3% dextrose in 0.18% saline (DS) as maintenance fluid. The duration of preoperative fast was noted and the blood glucose measured at induction, but before infusion of any intravenous fluid, and subsequently every 30 min. Data were analysed with Statistical Packages for the Social Sciences 16.0 (SPSS incorporated, Chicago Ill, USA). P < 0.05 was considered as significant. Results: The age range was 3 months to 15 years (mean = 4.9 ± 3.6 years); mean weight was 16.3 ± 7.8 kg. The mean duration of fasting was 13.4 ± 3.5 h (range = 4-18.5 h), but no child was hypoglycaemic throughout the study. The mean blood glucose in the LR group rose steadily from 5.18 ± 0.98 mmol/L post-induction to a peak value of 7.40 mmol/L at 120 min. In the DS group, the mean blood glucose level increased from the post-induction value of 5.56 ± 0.86 mmol/L to 12.7 ± 3.98 mmol/L at 120 min. Conclusion: Most children undergoing ambulatory surgery at our facility are still exposed to prolonged fasting time. Glucose containing fluid often administered as maintenance fluid to treat the presumed hypoglycaemia causes worsening hyperglycaemia, which may be harmful.